2021
DOI: 10.11646/zootaxa.5039.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Forficula iberica Steinmann, 1981 (Dermaptera: Forficulidae)

Abstract: Forficula iberica Steinmann, 1981 was described from Spain (Province of Zaragoza), but since its description it has remained an unknown taxon, usually ignored or treated as a synonym of F. auricularia Linnaeus, 1758. Field work in central Spain allowed us to collect some specimens of Dermaptera that matched the original description of F. iberica. In addition, the collection of the Museo Nacional de Ciencias Naturales (MNCN-CSIC, Spain) held some specimens assignable to F. iberica confused among other Iberian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Pygidium and male forceps morphology are traits widely used as diagnostic taxonomic characters, however these are characters with high intraspecific variability in earwigs (Dohrn 1867;Diajonov 1925;Ollason 1970;Simpson & Mayer 1990;Tomkins & Simmons 1996;García-París 2017;Kirstová et al 2020;Fontana et al 2021;García-París et al 2021;Jurado-Angulo et al 2021;Cuesta-Segura et al 2023). It has been recently demonstrated by morphological and molecular analyses (Fontana et al 2021;Jurado-Angulo et al 2021;Cuesta-Segura et al 2023), that the misinterpretation of the morphological variability of male cerci in Chelidura and Pseudochelidura led to errors in the determination of the geographic distribution of the species and in the delimitation of independent evolutionary units (e.g., species).…”
Section: Discussionmentioning
confidence: 99%
“…Pygidium and male forceps morphology are traits widely used as diagnostic taxonomic characters, however these are characters with high intraspecific variability in earwigs (Dohrn 1867;Diajonov 1925;Ollason 1970;Simpson & Mayer 1990;Tomkins & Simmons 1996;García-París 2017;Kirstová et al 2020;Fontana et al 2021;García-París et al 2021;Jurado-Angulo et al 2021;Cuesta-Segura et al 2023). It has been recently demonstrated by morphological and molecular analyses (Fontana et al 2021;Jurado-Angulo et al 2021;Cuesta-Segura et al 2023), that the misinterpretation of the morphological variability of male cerci in Chelidura and Pseudochelidura led to errors in the determination of the geographic distribution of the species and in the delimitation of independent evolutionary units (e.g., species).…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific variability of male cerci in earwigs is well known (Dohrn 1867;Diajonov 1925;Ollason 1970;Srivastava 1970;Mourier 1986;Simpson & Mayer 1990;Fontana et al 2021b;García-París et al 2021;Jurado-Angulo et al 2021); however, the levels of variability found in males of Pseudochelidura (Figs 2-3) are probably among the highest. It is thus somewhat counterintuitive that morphological differences in cerci shape between Pyrenean and Cantabrian populations (Figs 2-3) are relatively small and more limited than intrapopulational variability, but this is a situation relatively similar to that described for the French Massif Central and Pyrenean populations of Chelidura (Jurado-Angulo et al…”
Section: Pseudochelidura Cantabricamentioning
confidence: 97%
“…During a recent revision of the Iberian Dermaptera De Geer, 1773 (García-París 2017;González-Miguéns et al 2020;García-París et al 2021;Jurado-Angulo et al 2021), we had the opportunity of collecting and examining live specimens of Pseudochelidura from all the areas where the genus was reported in the Pyrenees and the Cantabrian Mountains. In addition, we had the opportunity to examine large series of Iberian specimens held at the Museo Nacional de Ciencias Naturales (MNCN, CSIC) (Madrid, Spain).…”
Section: Introductionmentioning
confidence: 99%